Medios, esfera pública y ciudadanía. ¿Qué políticas de comunicación para cuál sociedad? (2006)
This article aims at inquiring into the role communication policies play nowadays in thedemocratization of the public word, a fact which would certainly lead us to assume thatthe communication is a social right linked to the access, usage, practices, recognitions,and participation of citizens as individuals capable of formulating society projects.Communication is thus perceived as a necessarycondition for the conformation ofcomprising citizenships, as an indispensable element for the effective performance ofcivil and political rights and, hence, as a key factor to social integration.